Enhancement of Azo dyes Biodegradation by bioaugmentation and immobilization of microbial cells in wastewaters - Walaa Ahmed Ameen Al-Shareef (2014)
Arabic summary .
Reference (125-161).
(PH)- Cairo University :Faculty of Pharmacy ,2014.
Keywords: Microbiology and Immunology